Topical use of Bach Flowers Remedies in a specific vehicle: a therapeutic innovation (Research, Society and Development, 2023)
The use of Bach Flower Remedies (BFR) as an Integrative and Complementary Practice (ICP) in mental health care has been clearly recognized, especially after the 2020 pandemic. However, many users indicate the need for further practicality in the use of the BFR, since in the traditional method of internal use it is necessary to ingest the BFR 4 times a day, which is impractical for many patients (groups). In order to overcome this problem, a specific base cream for flower remedies was developed, to reduce the use of BFR for only 2 times a day. In the present work, with the aim of indicating the effectiveness of the specific base cream for flower remedies, dispensing the internal use, interviews with users of BFR and therapists was applied and combined with complementary radiesthesic tests, physical-chemical test (conductivity) and microbiology tests. The results indicated that the topical use BFR in a specific vehicle is effective, dispensing the traditional internal use, enhancing the therapeutic results, representing an important therapeutic innovation which facilitates the integrative and mental health care.